PREDICTABILITY IN THE PRODUCTIVE PROCESS OF THINNING AND CLEARCUTTING MECHANIZED OPERATIONS IN Pinus taeda L. - Garcia, Bruna Martins; Soares, Philipe Ricardo Casemiro; Sampietro, Jean Alberto; Fernandes, Caroline (Floresta, 2019)
Some organizations in the Brazilian forestry sector, especially in the activities carried out in forest stands, do not follow the development pace of other industries and the adoption rate of management and quality methodologies and tools. This study aimed to evaluate the predictability of timber harvesting process based on critical points identified in the selective thinning and clear cut operations. Interviews and Pareto chart were used, for the identification and evaluation of the critical points, respectively, and for the evaluation of the process, it was used the Statistical Process Control (SPC) by attributes and variables in the main failures. In the interviews conducted with workers, seven critical points were identified. The evaluation with Pareto chart showed that 80% of the failures identified during harvest are attributed to the damage to the remaining trees, sorting (measures of length and diameter of the product) and stump height. Among the possible causes of the critical points are problems with employees’ training, regular maintenance of machinery and operations planning. In the evaluation with the CEP, the control charts indicated that the sorting and stump height, although within the limits specified by the company, was considered unstable and unpredictable